Efeito vasorelaxante dos isômeros (+) e (-)-linalol em artéria mesentérica de rato - Cunha, Patrícia Santos (2013)
Linalool is a monoterpene can be biosynthesized by some plants in the racemic form, ( })-linalool, or in the form of enantiomers, (+)-linalool or (-)-linalool. The evaluation the activity of pure isomers has become important in the discovery of new drugs with improved therapeutic potential and a lower rate of adverse effects. So, the objective of the present study was to evaluate the vasorelaxant action induced by the enantiomers, (+) and (-)-linalool in rat superior mesenteric artery, besides seeks to elucidate the mechanisms of action involved in this effect. For both, male Wistar rats (200 . 300 g) were euthanized by exsanguination under anesthesia and superior mesenteric artery was removed. Rings were obtained (1-2 mm) this artery, and were mounted in organ baths containing 10 mL of Tyrode fs solution at 37 C and gassed with carbogen. For isometric tension recordings, each ring was suspended by cotton thread fixed in a force transducer connected to an acquisition system. In rings with functional endothelium pre-contracted with 10 ÊL of phenylephrine, both enantiomers were able to induce significant concentration-dependent vasorelaxation. Such as the effect presented by the (-)-linalool (Emax = 75 } 3%, n = 6) were higher than those for the (+)-linalool (Emax = 41 } 3%, n = 4), sought to evaluate the mechanism of action involved in their action vasorelaxant. In rings without functional endothelium, the vasorelaxation induced by (-)-linalool was significantly attenuated compared to the condition where the rings with functional endothelium were pre-contracted with phenylephrine (Emax = 55 } 1.5%, n = 5). Similar results were obtained after incubation with 10-8 M of atropine, an antagonist of muscarinic receptors (Emax = 50 } 5 %; n = 5); or with 10-4 M of L-NAME, an inhibitor of NO synthesis (Emax = 57 } 5 %; n = 6); or with 30 ÊM of hydroxocobalamin, a NO scavenger (Emax = 45 } 5 %; n = 6). In rings without functional endothelium incubated with 1 mM TEA, a blocker of non-selective K+ channels, the vasorelaxation induced by (-)-linalool had not changed significantly (Emax = 70 } 4 %; n = 4). However, in endothelium-denuded rings pre-contracted with KCl 80 mM, the oil-induced relaxation was significantly higher than that obtained without functional endothelium in rings pre-contracted with phenylephrine (Emax = 92 } 2 %; n = 5). In addition, isolated concentrations of (-)-linalool significantly reduced the contractions induced by CaCl2 (10-6 . 10-2 M) or by Na3VO4 (10-5 . 3 x 10-2 M), a non-selective inhibitor of protein tyrosine phosphatases. These results suggest that the effects induced by linalool occur mainly by the action of one of its isomers, the (-)-linalool. This isomer produces an effect vasorelaxant in rat superior mesenteric artery which is in part, dependent on the endothelium which is given by the activation of muscarinic receptors and the NO release. Furthermore, the endothelium-independent vasorelaxation is due to inhibition of calcium channel voltage-sensitive and involves the sensitization of the contractile machinery in vascular smooth muscle.